MAPPING OF MARINE PLANTS DISTRIBUTIONS IN NORTH COASTAL AREA OF SUMBAWA REGENCY USING ALOS/AVNIR-2 DATA - Astuti, S.P.; Osawa, T.; Merit, I N. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 5 No 1, 2012)
The exploitation and management of water resource be more beneficial, if preceded by study which includes biological aspect besides physics and chemical parameter of waters. The biological aspects study can be conducted by monitoring the change of ecosystem (biomonitoring). One of study that entangles biomonitoring is the research concerning change of marine plants. Marine plants consists of seagrasses and seaweeds. Using ALOS/AVNIR-2 data in this research because it has 3 visible bands (blue, green, and red) with 10 meter spacial resolutions can penetrate into water column. Aims of research were (1) to know combinations of bands in ALOS/AVNIR-2 data was better in Lyzenga method applying to mapping marine plants, (2) to know the general species of marine plants in north coastal area of Sumbawa regency. Lyzenga method was used in image processing process to know the combination of bands which have better for mapping marine plants. Preliminary steps of image processing were image cropping, geometric correction and radiometric correction. Water column effect was reduced by Lyzenga algorithm. Six classes were determined by multispectral classification process i.e. seagrass, seaweeds, coral, hard sand and rubble of coral, and substratum. Field surveys has done to identify the accuracy level. The accuracy method by Lillesand and Kiefer (1990) was used in this research. The result of accuracy test show for image band 1 and band 2 combination given better visual object benthic than another combinations of bands, with overall accuracy was 86.67%. Seagrass found in north coastal area of Sumbawa regency consist of four species there were Cymodocea rotundata, Enhalus acoroides, Syringodium isoetifolium, and Halophila ovalis with width equal to 835.37 ha, while seaweeds were found equal to five species there were Euchema cottoni, Euchema cottoni ssp sakul, Halimeda sp, Padina sp, and Sargasum duplicatum with width equal to 269,16 ha.
Keywords: Distribution of marine plants, Lyzenga method and ALOS data.